CULTURAL AND ECONOMIC SIGNIFICANCE OF RURAL WOMEN AND HANDLOOM IN MANIPUR - Lisam, Silvia (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The paper attempts to study the correlation between women and weaving in the economic and cultural context of Manipur. It tries to bring out the significance of handloom sector in preserving and promoting the rich cultural and historical values of Manipur. The paper tries to show that weaving also enhances the economic and social status of rural women in Manipur. The paper examines the cultural and economic significance of handloom in the lives of women in the rural sector of Manipur.